Implications of the Socio-Scientific Issues Approach on Students' Creative Thinking Skills in Science Learning: A Systematic Literature Review - Wanda Yudi Astari; I Wayan Redhana; I Nyoman Tika (Postgraduate, University of Mataram, 2025)
Science learning through the Socio-Scientific Issues (SSI) approach aims to help students understand scientific concepts and develop creative thinking skills through engagement with socially relevant contexts. However, despite its potential, students often struggle to generate and express creative ideas when dealing with scientific problems, suggesting that the creative dimension of SSI based learning is not yet fully realized in practice. Previous studies have demonstrated SSI’s effectiveness in enhancing scientific literacy, critical thinking, and argumentation, yet research on its role in fostering creative thinking remains limited. This study conducts a systematic literature review (SLR) to analyze how SSI based learning influences students’ creative thinking skills. The review includes international and national articles indexed in Scopus, Sinta 1–4, and open-access international proceedings published between 2021 and 2025. Selected studies discuss the implementation of SSI in school-level science learning using quantitative, qualitative, R&D, or mixed-methods designs. From 17 reviewed articles, quantitative approaches were found to be predominant. The findings indicate that SSI-based science learning can promote students’ flexible, early, and open-minded thinking in addressing scientific issues, thereby supporting the development of creative ideas.